Strategic Adaptation and Cultural Resilience in Indigenous Communities Facing Modernization Pressures - Sokk, Vutthy; Sihamoni, Norodom; Sokha, Kem; Samrin, Heng (Journal Social Humanity Perspective, 2024)
Inspired by the body of literature of the cultural convergence studies, this qualitative study will explore the issues behind the influence of modernization on indigenous cultural systems with respect to how the traditional communities negotiate the process of cultural continuity relative to the external socio-economic forces. Presented in the context of management, the study examines the strategies of adaptation and mechanisms of cultural governance those used by an indigenous community subjected to growing exposure towards the modernity of the institutions, technologies, and values. By deep level interviewing, participant observation and through document analysis, the research shows, that although modernization removes the conventional languages and rituals, it also triggers selective adaption which maintains the essence of cultural values. Instead of considering the existence of the opposing forces of tradition and modernity, the research identified that negotiation is a dynamic process of finding a balance between modern tools including such tools as digital media and formal education and the norms that held their ancestors together to maintain identity and cohesion. It is seen as a type of cultural management as a selective adaptation or an issue of resilience, stakeholder responsiveness, and ambidextrous governance. Also, the study refutes the prevalent developmental models that view indigenous knowledge systems as outdated, and the studies encourage the presence of more accommodating and culturally-based policy systems. The practice of locating indigenous agency in the current management theory allows contributing to the rising debate on adaptive systems, organizational resilience, and knowledge governance. It exhorts policy makers, aid groups and academicians to accept indigenous traditions as being not a barrier to modernization but as dynamic resources in healthy and fair modernization.